Implementation Of The Viola Jones Algorithm For Face Detection And Tracking On Robots With Limited Computation Power - Bezhanovski, Dimitar; Stankovski, Aleksandar (My University, 2022)
This paper aims at presenting how to implement face detection and tracking on a low powered robot that uses hardware such as the Raspberry Pi using the Viola Jones algorithm. With face detection and tracking implemented, the robot can follow the movement of a person, and move accordingly.